Group A emergency release plasma in trauma patients requiring massive transfusion - de Roulet, Amory (J Trauma Acute Care Surg, 2020)
BACKGROUND: Both group A and AB plasma have been approved for emergency release transfusion in acutely bleeding trauma patients prior to blood grouping being performed. The safety profile associated with this practice has not been well characterized, particularly in patients requiring massive transfusion. METHODS: This secondary analysis of the PROPPR trial examined whether exposure to group A emergency release plasma (ERP) was non-inferior to group AB ERP. We also examined patients whose blood groups were compatible versus incompatible with group A ERP. Outcomes included 30-day mortality and complication rates including systemic inflammatory response syndrome (SIRS), infection, renal injury, pulmonary dysfunction, and thromboembolism. RESULTS: Of the 680 patients predicted to receive a massive transfusion, 584 (85.9%) received at least 1 unit of ERP. Of the 584 patients analyzed, 462 (79.1%) received group AB and 122 (20.9%) received group A ERP. Using a hazard ratio (HR) of 1.35 as the non-inferiority margin, transfusion with group A versus group AB ERP was not associated with increased thromboembolic rates (HR 0.52, 95% CI 0.31–0.90). Mortality (HR 1.15, 95%CI 0.91–1.45) and non-fatal complication rates (HR 1.24, 95% CI 0.87–1.77) were inconclusive. In the subgroup analysis, transfusion with incompatible ERP (group B or AB patients receiving group A ERP) was not associated with increased nonfatal complications (HR=1.02, 95%CI 0.80–1.30). There were no reported hemolytic transfusion reactions. CONCLUSION: The use of emergency release plasma is common in patients requiring massive transfusion and facilitates the rapid balanced resuscitation of patients who have sustained blood loss. Group A emergency release plasma is an acceptable option for patients requiring massive transfusion, especially if group AB emergency release plasma is not readily available. STUDY TYPE: Prognostic Level III, Therapeutic / Care Management Level III